Makt, motmakt og praksis Bidrag til kritisk refleksjon innen diakoni og velferd - Lid, Inger Marie; Wyller, Trygve (Cappelen Damm Akademisk/NOASP (Nordic Open Access Scholarly Publishing), 2022)
Which voices, bodies and practices have expressed critical powerlessness in the face of institutional power, and who is expressing this today? What is at play, and what is the root of this powerlessness? These questions are at the core of this book. With Michel Foucault's theory of power and powerlessness as a point of departure, the contributing authors analyze and discuss the many conflicts and tension that arise when service users and patients take (or relinquish) a particular position. Institutions and professional practitioners have used and still use traditions, theories and methods that often weaken more than strengthen service users', patients' and clients' own volition and subjectivity. The chapters are by researchers in a variety of disciplines including theology, nursing, ethics, child welfare, disability research, history, diakonia, and social work. In the context of these fields, recognizing and emphasizing people's dignity and promoting equity are explored. But both historically and at present, research and experience show that the opposite also occurs. The ethical takes place between power, powerlessness and practice.